NATIONAL POLICY IN REFERENCE TO LABOR REMUNERATION AND ITS INFLUENCE ON POVERTY DYNAMICS IN A REGION - Kuklin А. А.; Leontieva А. G. (Экономика региона, 2010)
The paper emphasizes urgent issues regarding labor remuneration, which need to be settled along with adoption of socioeconomic policy aimed at critical reduction in size of the poor population.